METHOD AND APPARATUS - ARNOLD PAUL DOUGLAS; PROCINO IMMACOLATA (2019)
A method of operating an IMS cell, the method comprising obtaining first ion mobility spectrometry (IMS) data indicating the time of flight of ions through a drift gas of an IMS drift chamber, identifying, in the first IMS data, a reference feature associated with a selected group of ions; providing a dose of water vapour into the IMS cell to shift the reference feature to a selected time interval; and controlling dosing of water vapour into the drift gas based on second IMS data obtained using the IMS drift chamber to keep the reference feature within the selected time interval. 本发明公开了一种操作IMS单元的方法，所述方法包括：获得第一离子迁移谱(IMS)数据，所述第一IMS数据指示离子在IMS漂移室的漂移气体中飞行的时间；在所述第一IMS数据中，识别与所选离子组相关的参考特征；向所述IMS单元提供一定剂量的水蒸气，以将所述参考特征移动至选定时间间隔；以及根据使用所述IMS漂移室获得的第二IMS数据，控制向所述漂移气体中定量添加水蒸气，以使所述参考特征保持在所述选定时间间隔内。